Smart Grid Design and Simulation for Goma TMK Substation Regulation - Umaru, Kalyankolo; Magana, Ajabu Elie (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2026)
Power distribution networks in places like Goma, Democratic Republic of Congo, face the challenges of voltage control, energy loss, and power quality because they depend mainly on manual control provided at substations such as TMK. This study proposes a smart grid solution for automated voltage regulation through On-Load Tap Changer (OLTC) control for inefficiencies stemming from the above challenges using a Programmable Logic Controller (PLC). The system utilizes real-time electrical parameters monitoring, thereby employing dynamic adjustment processes to ensure voltage levels are kept at their optimum, as well as limiting overcurrent and improving thermal stability. The hybrid simulation approach uses Siemens TIA Portal for PLC logic and MATLAB Simulink to check the system's dynamic analysis under varied loads and faults. The results proved to enhance voltage stability and operational efficiency, and robustness while minimizing human intervention. The architecture is amenable to SCADA integration and distributed energy resources for future incorporation, thus providing a scalable solution to aging grids in resource-poor settings.